Probiotic supplementation for 24 weeks in patients with non-alcoholic steatohepatitis: the PROBILIVER randomized clinical trial - Silva-Sperb, Amanda Souza; Moraes, Helena Abadie; Barcelos, Samantha Thifani Alrutz; de Moura, Bruna Concheski; Longo, Larisse; Michalczuk, Matheus Truccolo; Cerski, Carlos Thadeu Schmidt; Uribe-Cruz, Carolina; da Silveira, Themis Reverbel; Álvares-da-Silva, Mário Reis; Dall’Alba, Valesca (Frontiers in Nutrition, 2024)
Considering the increasing prevalence of nonalcoholic steatohepatitis (NASH) and treatment gaps, this study aimed to evaluate the effect of probiotic supplementation on liver function markers, nutritional and clinical parameters. This double-blind, randomized clinical trial (ClinicalTrials.gov ID: NCT0346782) included adult outpatients with biopsy-proven NASH. The intervention consisted of 24 weeks of supplementation with probiotic mix Lactobacillus acidophilus (1 x 10 9 CFU) + Lactobacillus rhamnosus (1 x 10 9 CFU) + Lactobacillus paracasei (1 x 10 9 CFU) + Bifidobacterium lactis (1 x 10 9 CFU) or placebo, twice a day. The following parameters were evaluated: demographic and clinical data, transient elastography (FibroScan), liver enzymes, NAFLD fibrosis score, Fatty Liver Index, laboratory assessment, serum concentration of toll-like receptor-4 (sTLR-4) and of cytokeratin-18 (CK-18), anthropometric data, dietary intake, and physical activity. Regarding data analysis, the comparison between groups was based on the delta of the difference of each variable analyzed (value at the end of treatment minus the baseline value) using the t test for independent samples or the Mann-Whitney U test.Forty-four patients with NASH completed the trial (51.4 ±11.6 years). At baseline, 87% had mild liver fibrosis degree at biopsy, normal values of liver enzymes, values of the transient elastography consistent with grade 1 fibrosis in both groups, increased waist circumference (WC), BMI 30.97 kg/m 2 and 76% presented metabolic syndrome (MetS).After intervention, no differences were observed between the probiotic and placebo groups as for MetS, WC, BMI, scores or liver enzymes (p > 0.05 for all). The elastography values remained consistent with grade 1 fibrosis in both groups. Although CK18 was reduced in both groups, a larger effect size was noted in the probiotic group (D=1.336).sTLR-4 was also reduced in both groups, with no difference between groups (p = 0.885).Intervention with probiotics in early stages of NASH demonstrated to be unable to promote a significant change in hepatic and clinical parameters.